TUNING (CIVIL) ENGINEERING: THE 2013 EU-CHINA STUDY - Giuliano Augusti (2013)
Tuning Educational Structures is a university-driven process, developed in Europe to implement the Bologna Reforms, which offers a universal approach to higher educational reforms both at the macro-level of entire higher educational institutions and at the micro-level of individual disciplines or subject areas. The Tuning approach consists of a methodology to (re-)design, develop, implement and evaluate study programmes for each cycle (bachelors, masters and doctoral). Tuning initial (and still basic) subjects did not include engineering, contrary to what happens in all most recent and current initiatives, like the EU-China Tuning Study, started in March 2013 with a Preliminary Meeting in Xian. For this study, that will be summarized in a paper at the SEFI Conference 2013, three subject areas have been chosen, in consultations with the Chinese authorities, namely Education Sciences, Business, and Engineering (with special emphasis on Civil Engineering). The Authors of this paper are the European experts in the engineering area. They will assist the involved Chinese academics in pursuing the project objectives, which are: a) Development of conceptual frameworks tailored to the Chinese situation. b) Organisation of the consultation surveys in close cooperation with the different sectoral / subject area groups. Analysing of data which result from the consultation and comparison of those data with the outcomes of consultations executed in other regions of the world. c) Preparation of a report which identifies communalities and differences between the European and the Chinese higher education systems, offers mutually acknowledged criteria for quality enhancement and assurance and practical tools and mechanisms for mutual recognition of (parts of) academic studies. d) Preparation of intermediate reports regarding the progress of the study and a final report with respect to its outcomes. Further explanation of progress and outcomes will be done at face-to-face meetings in Brussels.